Development and use of a population based injury surveillance system: the All Wales Injury Surveillance System (AWISS). Issue 1 (1st March 2002) - Lyons, R A; Jones, S; Kemp, A; Sibert, J; Shepherd, J; Richmond, P; Bartlett, C; Palmer, S R
Abstract : This report details the development and use of a population based emergency room surveillance system in the UK. Despite some difficulties in accessing high quality data the system has stimulated a considerable number of research and intervention projects. While surveillance systems with high quality data collection and coding parameters remain the gold standard, imperfect systems, particularly if population based, can play a substantial part in stimulating injury prevention initiatives.